Стратегічні напрями модернізації житлового фонду як запорука енергетичної безпеки України - Матвійчук, Наталія Миколаївна; Matviichuk, Nataliia M.; Черчик, Лариса Миколаївна; Cherchyk, Larysa M.; Коленда, Наталія Вікторівна; Kolenda, Nataliia V.; Шульська, Наталія Миколаївна; Shulska, Nataliia M. (ДВНЗ «Університет банківської справи», 2018)
В статті обгрунтовано необхідність розроблення комплексної довгострокової стратегії модернізації застарілого та енергоємного житлового фонду України з метою забезпечення його енергоефективності та підвищення енергетичної безпеки держави. Запропонована стратегія включає: формування інституційного середовища через створення ефективних правових інструментів та відповідної інфраструктури ринку, джерела та механізми фінансування заходів з енергозбереження та енергоефективності, інструменти стимулювання власників та співвласників будівель до залучення в програми енергоефективності, напрями реформування житлових субсидій з метою підвищення їх стимулюючої стосовно енергоефективності ролі, створення сприятливого інвестиційного клімату для інвестування в енергоефективність, стимулювання ринку енергетичного сервісу та впровадження нових прогресивних енергозберігаючих технологій. The article substantiates the necessity of developing a comprehensive longterm strategy for modernization of an outdated and energy-intensive housing stock of Ukraine in order to ensure its energy efficiency and increase the energy security of the state. In many countries of the world, such strategies exist and describe in detail all legal, financial and technical instruments for increasing the energy efficiency of the housing stock. The proposed strategy includes: the formation of an institutional environment through the creation of effective legal instruments and appropriate market infrastructure, sources and mechanisms for funding energy efficiency measures, incentives for owners of buildings to be included in energy efficiency programs, housing subsidy reform to increase their incentive for energy efficiency role, creating a favorable investment climate for investing in energy efficiency, stimulate energy services market and implementing new energy technologies. An efficient modernization of the housing stock will have a socio-economic effect for the population and the state. The implementation of the proposed measures aimed at increasing the energy efficiency of residential buildings will stimulate construction, the market of energy-saving goods and services, create jobs and additional revenues to the budget. For the population it will significantly reduce the cost of housing services and influence the amount of their consumption. As a result of the certification of energy efficiency of buildings, demand for energy efficient housing and its price on the real estate market will increase. Increasing the energy efficiency of Ukraine's housing stock will improve energy security indicators such as energy consumption per capita and energy intensity of GDP, reduce expenditures on energy purchases and payment of housing subsidies.
Strategic directions of modernization of housing as a basis of Ukraine's energy security
Keywords: енергоефективність; energy efficiency; житловий фонд; housing stock; модернізація житлового фонду; housing stock modernization; житлові субсидії; housing subsidies; сертифікат енергетичної ефективності будівлі; energy efficiency certificate of a building; енергосервіс; energy service; ЕСКО; ESCO's